Molecular-phylogenetic characterization of the microbiota in ulcerated and non-ulcerated regions in the patients with Crohn's disease. - Qiurong Li (Public Library of Science (PLoS), 2012)
Background The dysbiosis of intestinal microbiota has been established in Crohn's disease (CD), but the molecular characterization of this dysbiosis in Chinese subjects with CD remains unclear. This study aims to investigate the predominant bacterial composition of the faecal and mucosal-associated microbiota in Chinese CD patients using culture-independent techniques. Methods/principal findings Eighteen patients with CD and 9 healthy controls were included in this study. The faeces and the intestinal mucosal tissues from the ulcerated and nonulcerated sites were subjected to bacterial community fingerprinting using denaturing gradient gel electrophoresis (DGGE). The predominant bacterial composition in the faeces and mucosa was determined with DNA sequencing and BLAST. We showed that the bacterial diversity in the faeces of CD patients was reduced compared with that in healthy controls (p<0.01). The faecal bacterial dysbiosis of the patients was characterized by an elevated abundance of γ-Proteobacteria (especially Escherichia coli and Shigella flexneri) and a reduced proportion of Bacteroidetes and Firmicutes. Five bacterial species defined the microbiota imbalance of the ulcerated mucosa in CD, including an increase in Escherichia coli, a decrease in Faecalibacterium prausnitzii, Lactobacillus coleohominis, Bacteroides sp and Streptococcus gallolyticus in the bacterial community as compared with the nonulcerated (p<0.01). Conclusions/significance This is the first description of intestinal microbiota dysbiosis in Chinese CD patients. These results allow a better understanding of the faecal and mucosal microbiota in CD, showing a predominance of some opportunistic pathogenic bacteria and a decrease in beneficial bacterial species. The findings may provide novel insights into the pathogenesis of CD in Chinese population.